Evaluation of Vocational School Pratic Program CIPP Model - ., Alexsandra; ., Ganefri; ., Usmeldi (Journal of Education Reseach and Evaluation, 2019)
The implementation of the vocational field work practice program is not in line with school expectations, the school still faces difficulties in finding a place to work in accordance with the expertise of students, the supervisor does not periodically monitor the business world of industry, lack of student discipline, the results of the field work practice program is declining, and the evaluation of field work practice programs has never been done at the Ketaping Aviation Vocational School. This study uses the CIPP program evaluation model (Context, Input, Process, Product) with a combination of balanced mixed model research methods and implemented at SMK. Qualitative research respondents were the head of the field work practice program, the head of the safety program, the supervisor, the field instructor. Quantitative research sample is class XII students who carry out practical work program in semester 3 a total of 45 samples. Data collection techniques data collection through questionnaires, documentation and interviews. Data analysis techniques were carried out on each quantitative and qualitative method, then the results of the analysis were combined to find mutually reinforcing or conflicting data and deepen the finding data. The research findings show that the context component is in the good category Input components are obtained by enough categories, the process components are obtained by enough categories and the results components are obtained by enough categories. It can be concluded that the field work practice program of Ketaping Aviation School is of sufficient value so that it needs improvement in all aspects of the components.